AB1060 Bisphosphonate intravenous allows a rapid contrast of pain in complex regional pain syndrome (CRPS). (23rd January 2014) - Bartoli, F.; Fiori, G.; Peruzzi, F.; Galluccio, F.; Cappelli, S.; Denaro, V.; Guidi, G.; Pfanner, S.; Ceruso, M.; Matucci-Cerinic, M.
Abstract : Background: The treatment of CRPS remains controversial, but multidisciplinary and interdisciplinary approaches seem to be inevitable to prevent long-standing or permanent disability (1). Bisphosphonates, apart from their antiresorptive activity, could also have other properties through a specific analgesic or anti-inflammatory effect.Bisphosphonate therapy has been shown to be effective in single cases of CRPS (2). Objectives: to evaluate the efficacyof intravenous compared with intramuscular bisphosphonates in reducing pain in patients with CRPS. Methods: 14 patients (one male and 13 females; mean age 64.3±8 years) diagnosed with CRPS of carpal and metacarpals bones (confirmed by clinical and MRI) from two weeks, were treated with non-steroidal anti-inflammatory drugs (NSAID), supplemental calcium and Vitamin D, physical therapy and clodronate. Seven patients were treated with iv (Group A) and seven with im clodronate (Group B) for 2 weeks. Then all patients were subjected to im clodronate 100 mg/weekly for 3 months. Pain scales (VAS 0-100) and joint examination were performed before, after one week and after 3 months of clodronate therapy. Results: pain was 92.7±12 mm in group A and 91±7.5 mm in group B, before starting clodronate (t0). Clodronate reduces pain significantly (p=0.0001) in both groups after one week of therapy, but reduction of pain was significantly higher (p=0.0001) in patients treated with iv clodronate (VAS 21.8±7 mm in group A vs 48.2±9.1 mm in group B). After 3months, nostatistical significant difference (p=0.7) in painwas found. Rapid reduction of pain in group A is associated also to a rapid reductionof hyperhidrosis, edema and joint stiffness after one week of therapy.No adverse effects were reported during therapy. Conclusions: Iv clodronate achieves a rapid reduction of pain compared to im formulation, in patients with CRPS. Early intervention and reduction of pain is also associated with a rapid clinical improvement that might help in the prevention of long-standing disability. References: Tran de QH, Duong S, Bertini P, Finlayson RJ. Treatment of complex regional pain syndrome: a review of the evidence. Simm PJ, Briody J, McQuade M, Munns CF. The successful use of pamidronate in an 11-year-old girl with complex regional pain syndrome: response to treatment demonstrated by serial peripheral quantitative computerised tomographic scans. Bone 2010 Apr;46(4):885-8. Epub 2009 Dec 5. Disclosure of Interest: None Declared